KARNAVAL SATANIC BRAZIL DALAM PEMIKIRAN AQIDAH IBNU QAYYIM AL-JAWZIYYAH - REZA, REZA DWI ARIYANI; Winarto (EL-ADABI : Jurnal Studi Islam, 2023)
Carnival is an event that is held at a certain time and can be both large and small scale. Carnival can be considered sacred if it is related to belief and can be considered as a tradition of a region with the aim of preserving culture. In the research being studied is a carnival with a satanic theme and held in Brazil. Satanic is a devil worshiping sect. In Brazil, there are very few people who adhere to satanic because the majority religion in Brazil is Catholicism. There are two main issues that will be studied, first is the satanic carnival in the perspective of the thought of the aqidah of Ibn Qayyim Al-Jawziyyah, and second is the response to how we respond to the satanic carnival that occurred in Brazil. The event drew a lot of negative criticism from the general public because after the carnival a disaster occurred which almost destroyed several cities in Brazil. However, there are not many who criticize the side of the carnival, such as the reason for the carnival being held and why there is a parade with a satanic theme. The researcher uses an analysis of the aqidah of Ibn Qayyim Al-Jawziyyah in the translation of his book Mawaridul Aman Al-Muntaqa min Ighatsatul Lahfan min Masyayidisy Syaithan (Heart Management: Paralyzing the Weapons of Satan. In this study using a qualitative method with a descriptive approach which is a type of research with the process of obtaining data is as it is. The researcher presents data obtained from the results of literature and document studies. By analyzing the data by processing it so that conclusions can be presented. The conclusion in this study is that there are two views, namely cultural elements and Islamic aqeedah. According to cultural elements, if indeed If it contains unifying values ​​such as harmony and harmony, respect for this culture is needed. However, when viewed from the perspective of Islamic aqeedah, satanic festivals can be classified as damaging aqidah if there is an element of shirk in them, such as worship of the devil.